Pengembangan E-Module Berbasis Education for Sustainable Development untuk Melatihkan Kompetensi Berpikir Kritis pada Siswa - Riska Novianti; Suhendar Suhendar; Jujun Ratnasari (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
This study aims to develop an e-module that is integrated with education for sustainable development to train students' critical thinking competencies on the subject of the human digestive system. The method used in this study is a type of quantitative method. The type of research is development (Research & Development) using the ADDIE research model (Analysis, Design, Development, Implementation, and Evaluation). The subjects used in the study were 45 students from class XI IPA 3 and XI IPA 4 at MA Negeri 2 Sukabumi City. The instruments used were assessments from material, media, and language experts, giving pretest and posttest questions, using attitude scale sheets, and response sheets to determine the effectiveness of the e-module and critical thinking competence in students. Research has results showing that: 1) validation or assessment by material experts shows that this e-module is valid, media and language experts say it is very valid with an average percentage of 82.3% ± 11.1; 2) the effectiveness test of the N-gain calculation states that the e-module is in the medium category with an average N-gain value of 0.52 ± 0.03; 3) the attitude scale sheet states that students have high critical thinking competence, the attitude scale is at a percentage of 77.4% ± 1.88 which is in the very good category; and 4) the response test states that this e-module is very valid to use with a percentage of 83.2% ± 11.6. Judging from the results and discussion, the development of e-module in the ADDIE model can train critical thinking competencies and is suitable for use in the learning process.